The pursuit of teacher quality: identifying some of the multiple discourses of quality that impact the work of teacher educators. Issue 3 (27th May 2019) - Churchward, Peter; Willis, Jill
ABSTRACT: Concerns with the readiness of beginning teachers has resulted in significant changes to ITE programs in Australia. Declining student performance in domestic and international assessments is being seen as a policy problem that can be addressed through policy solutions intended to lift the quality of teachers. While quality and performance measures are linked in this policy agenda, it is not clear how quality teacher and teaching are being defined. In this special issue exploring what teacher educators "should" know, it is reasonable for teacher educators to know more about the ideals of teacher and teaching quality against which they are held to account. Exploring the literature pertaining to the quality teacher discourse informing initial teacher education (ITE) programs, this paper is a thematic literature review relating to the discourses of teacher and teaching quality. Understanding how these discourses of quality interrelate and shape teacher education is an important and necessary consideration in the development of ITE programs.